Effect of Wheat Flour Concentration on Physicochemical and Sensory Properties of Cilembu Yam Chicken Nugget - Jennifer Elizabeth; Chatarina Yayuk Trisnawati; Anita Maya Sutedja (Food ScienTech Journal, 2025)
Cilembu yam is a yellow or orange yam that is abundantly available that is still minimally utilized in Indonesia. One alternative to diversify the utilization of cilembu yam is processing it into cilembu yam chicken nuggets. The 50% substitution of chicken meat with cilembu yam produces nuggets with a more attractive color and the taste of chicken is still felt and the sweetness is not prominent but the texture of the nuggets becomes too soft so it requires the addition of wheat flour as a filler and binder. The objective of this study was to determine the effect of wheat flour concentration on the physicochemical and sensory characteristics of cilembu yam-chicken nuggets. The research design used a single-factor randomized group design with four replications. The concentration of wheat flour added was 5%, 10%, 15%, 20%, 25%, and 30%. Data were analyzed with Analysis of Variance with α=5% then followed by the Duncan’s Multiple Range Test with α=5%. The results showed that as the concentration of wheat flour increased, the water holding capacity of the nugget batter as well as the hardness and toughness of the fried cilembu yam chicken nugget increased while the moisture content and juiceness decreased. Preference of bite ability increased up to 15% wheat flour concentration and was not significantly different from 20%. The use of wheat flour concentration up to 20% increased the preference of springiness but decreased the preference of juiceness to an acceptable level.